Offending and Victimization in the Digital Age: Comparing Correlates of Cybercrime and Traditional Offending-Only, Victimization-Only and the Victimization-Offending Overlap. Issue 1 (2nd January 2019) - Weulen Kranenbarg, Marleen; Holt, Thomas J.; van Gelder, Jean-Louis
ABSTRACT: Cybercrime research suggests that, analogous to traditional crime, victims are more likely to be offenders. This overlap could be caused by shared risk factors, but it is unclear if these are comparable to traditional risk factors. Utilizing a high risk sample of computer-dependent cyber-offenders and traditional offenders ( N = 535) we compare victimization, offending, and victimization-offending between cybercrime and traditional crime. Cybercrime results show a considerable victim-offender overlap and correlates like low self-control and routine activities partly explain differences in victimization, offending, and victimization-offending. Some cybercrime correlates are related to the digital context, but show similar patterns for cybercrime and traditional crime.